Interfacial Contact is Required for Metal‐Assisted Plasma Etching of Silicon. Issue 24 (21st October 2018) - Sun, Julia B.; Almquist, Benjamin D.
Abstract: For decades, fabrication of semiconductor devices has utilized well‐established etching techniques to create complex nanostructures in silicon. The most common dry process is reactive ion etching which fabricates nanostructures through the selective removal of unmasked silicon. Generalized enhancements of etching have been reported with mask‐enhanced etching with Al, Cr, Cu, and Ag masks, but there is a lack of reports exploring the ability of metallic films to catalytically enhance the local etching of silicon in plasmas. Here, metal‐assisted plasma etching (MAPE) is performed using patterned nanometers‐thick gold films to catalyze the etching of silicon in an SF6 /O2 mixed plasma, selectively increasing the rate of etching by over 1000%. The catalytic enhancement of etching requires direct Si‐metal interfacial contact, similar to metal‐assisted chemical etching (MACE), but is different in terms of the etching mechanism. The mechanism of MAPE is explored by characterizing the degree of enhancement as a function of Au catalyst configuration and relative oxygen feed concentration, along with the catalytic activities of other common MACE metals including Ag, Pt, and Cu. Abstract : Gold films have been shown to enhance the etching of silicon in fluorine‐based plasmas. By using bimetallic nanostructured particles, here it is shown that interfacial contact between Au and Si is required for enhanced etching. Ag is also shown to facilitate enhanced etching, whereas Pt and Cu do not, in contrast to metal‐enhanced etching of Si in liquid solutions.